Patterns and correlates of active commuting in adults with type 2 diabetes: cross-sectional evidence from UK Biobank. Issue 10 (8th October 2017) - Falconer, Catherine L; Cooper, Ashley R; Flint, Ellen
Abstract : Objectives: To describe the active commuting (AC) patterns of adults with type 2 diabetes and how these relate to physical activity and sedentary behaviour in UK Biobank. Social and environmental correlates of AC will also be explored. Design: Cross-sectional analysis of a cohort study. Settings: This is a population cohort of over 500 000 people recruited from 22 centres across the UK. Participants aged between 37 and 73 years were recruited between 2006 and 2010. Participants: 6896 participants with a self-reported type 2 diabetes diagnosis who reported commuting to work and had complete covariate data were included in the analysis. Exposure measures: Exposure measures were AC to work, measured as usual mode of transport. Outcome measures: Outcome measures were weekly minutes of moderate to vigorous physical activity (MVPA), hours/day of sedentary time and participation in active travel. Results: AC (reporting walking or cycling to work only) was reported by 5.5% of participants, with the great majority using the car to commute (80%). AC was associated with an additional 73 (95% CI 10.8 to 134.9) and 105 (95% CI 41.7 to 167.2) weekly minutes of MVPA for men and women, respectively. AC was associated with reduced sedentary time (β −1.1, 95% CI −1.6 to –0.7 hours/day for men; and β −0.8, 95% CI −1.2 to –0.3 hours/day for women). Deprivation and distance from home to work were identified as correlates of AC behaviour. Conclusions: Rates of AC are very low in adults with type 2 diabetes. However, AC offers a potentially sustainable solution to increasing physical activity and reducing sedentary behaviour. Therefore, strategies to improve the environment and encourage AC may help to increase population levels of physical activity and reduce the disease burden associated with type 2 diabetes.